Impact of the capital market on the transformation of the economy in Ukraine - Krupka, Stanisław (Technological and Economic Development of Economy, 2007)
The paper is dedicated to a thorough analysis of the formation of the securities market in Ukraine, which follows the hash transitional road to market economy full of political vibes and the fight of interest groups reflected in the so‐called “grey” or “black” economy. Therefore the path to developing the market of securities in Ukraine was not easy. An overview of the related laws and directives passed in Ukraine is presented with the author's comments, suggestions and scientific reasoning of how the market of securities developed then and what are the prospects for the future. With this purpose in mind, the author presents data on the legal efforts of the Ukrainian Government to prepare a fruitful soil for the development of securities market and discussed the obstacles, which posed and still pose threats for an adequate functioning of the Ukrainian market of securities. Some European comparisons are taken into account, especially from the Frontier's group countries.Kapitalo rinkos įtaka Ukrainos ekonomikos transformacijaiSantrauka. Straipsnyje pateikiama Ukrainos vertybinių popierių rinkos, kaip vienos iš kapitalo rinkos, formavimo istorinė lyginamoji analizė, apimanti 1991–2004 metus. Daug dėmesio skiriamas Ukrainos Vyriausybės pastangoms kurti teisinį vertybinių popierių rinkos pagrindą, apžvelgiami įstatymai ir direktyvos, teikiamos tolesnės šios rinkos plėtros tendencijos.Reikšminiai žodžiai: kapitalo rinka, vertybinių popierių rinka, pereinamoji ekonomika, Frontier šalių grupė, Ukraina.First Published Online: 21 Oct 2010